2013
DOI: 10.2478/s11686-013-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

First detection and genotyping of human-associated microsporidia in wild waterfowl of Slovakia

Abstract: A total of 47 avian faecal samples of wild waterfowl (great cormorant -Phalacrocorax carbo, great crested grebe -Podiceps cristatus, white stork -Ciconia ciconia) trapped in the eastern Slovakia were screened for the presence of human pathogenic microsporidia by microscopy and real-time SYBR Green PCR method using species primers and sequenced. Microscopic analysis showed presence in 32 samples (29 cormorants, 3 dippers). Microsporidial DNA (Encephalitozoon cuniculi genotype I) was identified in 19 faeces samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Besides Enterocytozoon spp. (Haro et al., 2006b, Lobo et al., 2006, Bart et al., 2008), E. hellem is a highly prevalent microsporidian species of birds (Słodkowicz-Kowalska et al., 2006, Malčeková et al., 2013). However, in most studies only one of several genera of microsporidia was tested for so that a direct comparison is not feasible.…”
Section: Orders Of Wild Animals Infected With Encephalitozoonmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides Enterocytozoon spp. (Haro et al., 2006b, Lobo et al., 2006, Bart et al., 2008), E. hellem is a highly prevalent microsporidian species of birds (Słodkowicz-Kowalska et al., 2006, Malčeková et al., 2013). However, in most studies only one of several genera of microsporidia was tested for so that a direct comparison is not feasible.…”
Section: Orders Of Wild Animals Infected With Encephalitozoonmentioning
confidence: 99%
“…Exposure to infected urban park pigeons might thus lead to zoonotic transmission of microsporidia (Haro et al., 2005). Especially waterfowl may be a major source of contamination of surface waters as they show very high infection rates with potentially zoonotic microsporidia (Graczyk et al., 2008, Malčeková et al., 2013). Furthermore, aquatic birds frequently defecate into water and usually have unlimited access to surface water used for drinking water production.…”
Section: Medical Implicationsmentioning
confidence: 99%
“…As shown, microsporidian species known to infect humans such as E. hellem are present in aquatic bird species including Anas platyrhynchos , Anser anser , Balearic pavonina , Cygnus atratus , C. melanocoryphus , C. olor and Coscoroba coscoroba (Słodkowicz-Kowalska et al 2006). The E. cuniculi (but not E. hellem , E. intestinalis or E. bieneusi ) was found in the Slovakian pilot study examining 40 samples of great cormorant feces at a relatively high prevalence of 42.5% (Malčeková et al 2013). The present study showed decidedly lower frequency of spores in investigated population of 125 birds indicating that the role of great cormorants in Microsporidia dispersion may be highly site specific.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms in humanSchelling et al 1999; Artois et al 2002; Iashkulov et al 2008  West Nile virusNorth-western area of the Caspian SeaMosquitoes are prime vectors, birds are main hostsWest Nile fever. Rarely neurological symptomsIashkulov et al 2008 Fungi MicrosporidiaSlovakia, Poland Encephalitozoon cuniculi was identified (Slovakia).Intestinal parasitosis, diarrheaMalčeková et al 2013; This studyProtozoan parasites  Cryptosporidium sp.Hungary, Netherlands, PolandThe exact genotype was not determinedIntestinal parasitosis, diarrheaMedema 1999; Plutzer and Tomor 2009; This study  Giardia sp.HungaryThe exact genotype was not determinedIntestinal parasitosis, diarrheaPlutzer and Tomor 2009 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation